ARM MUSCLE POWER AND TORSO FLEXIBILITY: KEY DETERMINANTS OF ROLL-KIP PROFICIENCY IN FLOOR EXERCISE - fitrah, muhammad fitrah mubarak (Universitas Muhammadiyah Kuningan, 2025)
This study aims to share the contribution of arm muscle strength and trunk flexibility to roll-kip performance in floor gymnastics in students of the Sports Coaching Education Study Program, Cenderawasih University. The background of the study was based on significant variations in roll-kip performance among students, allegedly due to reduced arm muscle strength and trunk flexibility. The research method used a quantitative correlational approach with a sample of 40 students selected purposively. Data were collected through push-up tests (arm muscle strength), trunk lift extension tests (torso flexibility), and roll-kip performance assessments by instructors. Data analysis used SPSS for correlation and multiple regression tests. The results showed a positive and significant relationship between arm muscle strength (r = 0.800; p < 0.05) and trunk flexibility (r = 0.796; p < 0.05) with roll-kip performance. The combined contribution of both variables was 73%, with trunk flexibility having a more dominant influence (1.663) than arm muscle strength (0.401). The conclusion of the study emphasizes the importance of training both aspects in a balanced manner in a floor gymnastics training program to improve performance in performing transition movements such as roll-kip.